Konsep Diri Pada Komunitas Punk di Kabupaten Garut - Zahara Farhan; Gingin Sugih Permana; Devi Ratnasari; Aas Astriani (Jurnal Medika Cendikia, 2021)
Self concept is the core of a person's personality development pattern that affects a person's personality traits or personality which is divided into five aspects including; body image, self ideal, self esteem, self role and self identity (Hariyanto, 2013). Punk community is a social image of street children whose existence is considered unsettling for residents. One of the factors causing their entry into the street environment is the low level of education. The low level of education possessed by the punk community has an impact on the emergence of uncontrolled behavior resulting in aggressive behavior (Tentama, 2013). The general objective of this study was to determine the self concept of the punk community in Garut Regency in 2018. The research design was descriptive, data collection was carried out in the District of Garut Kota on 95 punk children with a total sampling technique. Data collection using questionnaires and direct interviews. Data analysis with frequency distribution based on the median value of each aspect of self concept. The results showed that almost all of the self concept in the punk community (73.68%) was positive and almost half (26.32) was negative. The results of research on each aspect of the self concept of punk community showed that the body image was mostly (67.37%) positive, the ideal self was mostly (60%) positive, the self esteem was mostly (72.63%) high, the self role was half (50.53%) was negative, and self identity was mostly (53.68%) negative. The punk community values ​​themselves positively and feels more confident about doing activities in their daily lives and is able to accept themselves as they are. The negative stigma from society does not become an obstacle for them to behave well. The self concept of punk community in Garut Regency generally has a positive self concept